A Central Preoccupation that Constantly arises in Australian Culture - Rosie Kithren (Al-Qanṭara, 2022)
Abstract: A central preoccupation that constantly arises in Australian culture is the question of who ‘we’ are and where ‘we’ belong. So much is evident in independent women’s fashion magazine Russh, the focus of this article, in which pride and uncertainty about Australian identity (and fashionability) are representationally resolved through a sensual, girlish and white fashionable ideal. By closely analysing magazine issues selected from its archive, this article charts the ways that Russh imagines Australian fashion as both imbricated with global flows as well as reaching from the periphery towards where fashion really originates. It then reads the fashionable femininity represented in the magazine in light of settler colonial fantasies that imagine the actualisation of national character amongst the Australian landscape – a landscape in which white presence is positioned as originary. This fashionable ideal symbolically rejects cosmopolitanism through her ‘return to the bush’ whilst embodying fashion itself, thus reconciling the tension between far and near. As such, RUSSH can be read as actively reinforcing a hegemonic Australian imaginary that elides the diversity of contemporary Australian culture/s whilst escaping censure, because as a niche fashion magazine peopled with dreamy protagonists, its content is situated firmly within the realm of fashion’s fantasy.